Torque for an Inertial Piezoelectric Rotary Motor - Jichun Xing; Lizhong Xu (The Scientific World Journal)
For a novel inertial piezoelectric rotary motor, the equation of the strain energy in the piezoceramic bimorph and the equations of the strain energy and the kinetic energy in the rotor are given. Based on them, the dynamic equation of the motor is obtained. Using these equations, the inertial driving torque of the motor is investigated. The results show that the impulsive driving torque changes with changing peak voltage of the excitation signal, the piezoelectric stress constant, the thickness of the piezoceramic bimorph, and the rotor radius obviously. Tests about the motor torque are completed which verifies the theory analysis here in. The results can be used to design the operating performance of the motor.